Time Series Analysis of Chromophoric Dissolved Organic Matter (CDOM) at Perancak Estuary - Suryaputra, I Gusti Ngurah Agung (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This study aimed at determaining the effect of sea tides on changes of CDOM, in-situ parameters and nutrients on Perancak Estuary. The subject of this study was estuary water collected from Estuary Perancak and filtered using GF/F 0.7 μm with help of injection. The objects of this study were CDOM absorbance, nutrients concentration and parameters in-situ. Sampel collected every 1 hour once for 25 hours, were measured in-situ parameters. Filtered estuary water was placed into sample bottles and placed in a box was kept away from light. Absorbance and nutrients concentration were measured using UV-1800 Shimadzu UV-Vis Spectrophotometer. Absorbance spectral slope (S) and E2:E3 were calculated from the absorbance. Result shows that S275-295 and E2:E3 had a negative correlation with water level, while SR did not show any positive and negative correlation with water level. In addition most of in-situ parameters show a positive correlation with water level and some of nutrients show a negative correlation with water level.